The structure and content of the religious tourism destination image construct: an exploratory netnography of travelers’ reviews of Makkah and Medina - Zarkada, Anna K.; Kashif, Muhammad; Zainab (My University, 2024)
Purpose – This paper aims to examine the structure and content of religious tourism destination image through the reviews of visitors to Makkah and Medina, two of the world’s most popular Muslim pilgrimage sites. Design/methodology/approach – This is an exploratory netnographic study of the 913 reviews posted on TripAdvisor from 2018 to 2022. The structure (dimensions and attributes) and content (variables) comprising the construct of religious tourism destination image emerge through manual thematic analysis and confirmed through content analysis. Findings – Religious tourism destination image is a three-dimensional – cognitive, affective and conative – construct comprising both religion-specific, generally sacred and secular variables in a single, indivisible crystallization of experience. Practical implications – Destination marketing organizations and marketers of tourism enterprises should regularly analyze visitor reviews posted on social media and carefully manage all variables of the religious tourism destination image, specifically stressing the religious aspect. Originality/value – To the best of the authors’ knowledge, this is the first systematic analysis of the structure and content of religious tourism destination image based on detailed consumer evaluations and unprompted storytelling.
Keywords: tourism, social media, pilgrimage, netnography, religious tourism destination image